Affordable Oxygen Concentrator with PSA Technology - Bobby, J. Sofia; Bharath S; Madhankumar C; Sudharsanam K; Ummathullah U (Engineering Research: Perspectives on Recent Advances Vol. 1, 2024)
Atmospheric air typically consists of a mixture of gases, including nitrogen (78%), oxygen (21%), and trace amounts of other gases such as carbon dioxide (0.03%) and hydrogen. An oxygen concentrator is a device designed to extract and concentrate oxygen from ambient air by selectively removing nitrogen through a process known as Pressure Swing Adsorption (PSA). PSA technology is commonly used in oxygen concentrators, as it efficiently separates oxygen from the air using two adsorbent materials, typically zeolite. This process makes PSA-based concentrators more reliable and energy-efficient for delivering oxygen at medical-grade purity. PSA works by exploiting the molecular properties and affinity of gases for a zeolite (such as Natrolite) under varying pressure conditions to separate oxygen from the air. The oxygen concentrator utilizing this PSA technology is both cost-effective and efficient. Experimental results show that the system can produce oxygen with a purity of approximately 94.7% at flow rates of 0.5-3 L/min. This meets the needs of patients with Chronic Obstructive Pulmonary Disease (COPD), who require oxygen with a purity of at least 90% at similar flow rates. When compared to commercially available oxygen concentrators, the proposed system stands out for being highly cost-effective, lighter in weight, and producing less noise. Additionally, it demonstrates long-term efficiency with high oxygen purity. These features make it an ideal solution for individuals who cannot afford expensive oxygen concentrators available on the market.